AFFIXATION SYSTEM OF BALINESE LANGUAGE SPOKEN BY MUSLIM PEOPLE IN TEGALLINGGAH VILLAGE: A DESCRIPTIVE QUALITATIVE STUDY - Suardika, Kadek; Budasi, I Gede; Suprianti, G.A.P. (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2018)
This study aimed at describing the affixes: prefixes and suffixes of Balinese language spokenby Muslim people which belong to derivational and inflectional morpheme. This descriptive qualitativestudy involved 3 informants chosen based on a set criteria. The gained data were collected through observing,recording, and interviewing technique. The instruments in this study were classified into: maininstrument (the researcher) and secondary instruments (word list, observation sheet, digital recorder,and camera). The three processes in analyzing the data were data reduction, data display, and dataconclusion or verification. This study revealed nine prefixes and six suffixes of Balinese language spokenby Muslim people in Tegallinggah Village. The nine prefixes are classified into: 2 prefixes {mÓ™} andnÇÅ‹- which belong only to derivational morpheme, 4 prefixes ÊŒ, {kÓ™-}, {bÓ™}, and {Ó™-}, belong only toinflectional morpheme, 3 prefixes {Å‹Ç-}, {Å‹-}, and {m-} can belong to derivational and inflectional morpheme.Afterward, the six suffixes are classified into; there is no suffix which belong only to derivationalmorpheme, 4 suffixes {-Ä“}, {-Ç}, {-ÊŒÅ‹}, and {-Éªn} belong only to inflectional morpheme, 2 suffixes {-ÊŒn},dan {-n} can belong to derivational and inflectional morpheme.Key Words: prefixes, suffixes, Balinese language, derivational morpheme, inflectional morpheme